Low temperature processed ZnO thin film as electron transport layer for efficient perovskite solar cells - Mahmud, M.; Elumalai, Naveen Kumar; Upama, M.; Wang, D.; Chan, K.; Wright, M.; Xu, C.; Haque, F.; Uddin, A. (Elsevier BV * North-Holland, 2017)
Organic inorganic lead halide Perovskite photovoltaic devices are promising candidates for commercial application because of their high efficiency and low production cost. One integral part of these high efficiency solar cells is electron transport layer that provides the electron contact selectivity and mitigates recombination phenomena for enhanced device performance. However, high temperature sintering process of most widely used Titanium oxide electron transport layer or the sophisticated, time consuming processing with nanostructured electron extraction material is a fundamental barrier to mass production of Perovskite solar cell with roll-to-roll process. In this work, we have reported the application of simple, low temperature processed (<150 °C) sol-gel ZnO thin film as electron transport layer with efficient (PCE: 8.77%), highly reproducible Perovskite solar cell. Consecutive spin coating process has been implemented to find a multi-layer ZnO film that ensures high optical absorption in photoactive Perovskite layer by acting as a highly transmitting, less reflective, transparent layer. The optimized ZnO film also provides coherent surface morphology for the proper crystalline growth of overlying Perovskite layer and suppresses the deep trap states existing at the ZnO/perovskite interface. A systematic impedance spectroscopy study has been presented in this work to comprehend the improved device performance with the optimized multilayer electron transport material. The electronic properties like contact resistance, recombination resistance, flat-band potential and depletion width of the best performing device have been investigated. The interfacial charge transfer characteristics between methyl ammonium lead triiodide perovskite and low temperature solgel ZnO have also been elaborated based on the interface electronic properties.